Pemanfaatan game edukasi sebagai strategi inovatif dalam pembelajaran abad ke-21 - Novia Tri Hapsari; Prima Ratna Sari; Yogi Dwi Satrio (Universitas Negeri Surabaya, 2026)
Traditional learning approaches are often seen as less effective in enhancing student motivation and deep understanding, creating a need for more innovative instructional strategies. This study explores the use of game-based learning through the Quizizz platform as an interactive alternative to conventional teaching. The research focuses on the implementation of Quizizz in the Economic Education Study Program at the University of Jember. A descriptive qualitative case study approach was employed, involving 29 participants selected through purposive sampling. Data were collected through questionnaires, interviews, and documentation. The results indicate that Quizizz positively impacts both lecturers and students by creating a more active, enjoyable, and experience-based learning environment. It helps reduce academic pressure while improving learning motivation, critical thinking skills, and digital literacy. Despite these benefits, Quizizz should be used alongside other teaching methods and is most effective for reinforcing material and conducting formative assessments. Overall, Quizizz is considered a relevant learning tool that aligns with the characteristics of contemporary university students and supports the principles of 21st-century learning.